Netarsudil as an Adjunctive Therapy: Efficacy and Factors Contributing to a Favorable IOP-Lowering Effect - Sandy Samuel; Hani El Helwe; Cameron E. Neeson; Nathan Hall; Ryan Sameen Meshkin; Nino Odishelidze; Rebecca Ye; Ta C. Chang; David Solá-Del Valle (Journal of Ophthalmology)
Purpose. The aim of the study is to assess netarsudil’s intraocular pressure (IOP)-lowering potential when prescribed as an adjunctive agent, to examine the effect of baseline IOP on patients’ response to netarsudil, and to explore patients’ characteristics predictive of pronounced responses to netarsudil. Methods. This is a single-center, multiprovider retrospective cohort study set at Massachusetts Eye and Ear. Patients with a diagnosis of glaucoma or ocular hypertension on netarsudil and at least one other hypotensive agent for glaucoma who had at least one month of follow-up were included. Patients with additional procedures or glaucoma medication changes were excluded. The main outcome measures were IOP reduction, Kaplan–Meier survival analyses, netarsudil responder type, and complication rates. Results. 236 eyes of 236 patients were included. The mean baseline IOP was 19.06 ± 4.6 mmHg on an average of 4 ocular hypotensive medications. 196 (83.1%) patients experienced IOP reduction at the first follow-up visit of 2.84 ± 0.30 mmHg at 55.66 ± 51.89 days. IOP reduction at the second visit among these patients was 3.01 ± 0.44 mmHg at 133.24 ± 77.63 days. After starting netarsudil, 59% had a sustained response (median duration of 315 days), 25% had a robust response (>20% IOP reduction for at least 80% of visits), and 10% had a super response (>20% and >10 mmHg IOP reduction). Netarsudil was effective as an adjunctive therapy across all baseline IOP categories with greater relative IOP reduction in higher baseline IOP groups. Conclusions. Netarsudil is an effective adjunctive glaucoma therapy. IOP reductions between 2 and 3 mmHg are typical, but a minority had more pronounced and sustained effects (>10 mmHg). Further analysis is needed to assess specific demographic and clinical factors predictive of these robust responses.